PENINGKATAN KINERJA PENGADAAN BARANG PT. API METRA PALMA DENGAN METODE THEORY OF CONSTRAINT THINKING PROCESS - Kokoh Ronald Aruan; Lusia Vreyda A (Journal of Management and Business Review, 2011)
This study aimed to solve the problem of low performance at PT. Api Metra Palma (AMP). Procurement is an important aspect in the company because ineffective procurement process may cause disruption to the overall business process and hinder the operational capability of the company. This procurement problem has occurred at the company long enough, causing a variety of losses, and is a complex problem because it involves many functional parts of the company. Performance measurements for procurement are delivery performance and order fulfillment lead time. Indicators of low performance in the company's procurement are marked with the slow realization of the demand (more than one month) and the underachievement of Quality Objective (QO) of the Department of Procurement and General Affairs.The analysis framework employed the stages of TOC Thinking Process. This theory uses five application tools, namely: Current Reality Tree (CRT), Conflict Cloud (CC), Future Reality Tree (FRT), Prerequisite Tree (PT), and the Transition Tree (TT). Those tools were utilized to identify the key problem, develop solutions and determine the solution to the problem. All the stages were presented in the form of effect-cause-effect relationship in a system and were presented in a form of visual images through a Tree Diagram. This study used a new approach in the TOC Thinking Process, namely the three cloud approach/3-UDE Cloud. This approach can provide guidance for communicating with various parties within the company without creating any resistance through the exposure of conflict in the company. This theory also provides a means for the system to make continuous improvement through the reinforcing loop.This study resulted in the identified root causes of the procurement problem, namely the company’s inability to change the current resources (that support the procurement) to become more reliable. A General Injection to solve the conflicts that exist within the company is through the transformation of procurement resources to become reliable. The transformation is carried out upon human resources, information technology, and procurement methods. The transformation description of the resource procurement is achieved through the implementation of several programs, namely: Internal Technical Training, Holding Visit and Midyear Coordination Meeting, TI Integration for the Procurement of Goods, Network Improvement, Negotiation of Priority Scale Policy Change, Term of Payment (TOP), Early Warning System, and Improvement of Document Control. This study was also able to identify that the company’s paradigm of cost efficiency in all functions and which was derived in the company's policy only caused the company to lose the competitiveness due to the weakened procurement performance.